Optimizing librarian performance in improving the efficiency and quality of library services - Eny Supriati; ‎Hari Murbayanto‎; Laila Tri Nurmasari (IJAL (Indonesian Journal of Academic Librarianship), 2023)
Libraries, as educational institutions and information centers, are essential in providing efficient and quality services to their users. Librarians' performance is a crucial factor in achieving these goals. This study aims to optimize the performance of librarians to improve the efficiency and quality of library services. They use a qualitative approach with data collection through various sources, including documentation, interviews, and observations. The collected data is analyzed through three steps, namely data reduction, data presentation, then drawing data conclusions to identify factors that affect librarian performance and analyze the implications with the efficiency and quality of library services. The results showed that several factors can affect the performance of librarians. These factors include librarians' knowledge and skills, management support, use of information technology, collaboration between librarians, and work motivation. This research also identifies several strategies that can be applied to improve the performance of librarians, including training and development, improved communication, and cooperation between librarians. By optimizing librarian performance by implementing appropriate strategies, libraries can achieve higher operational efficiency and improve the quality of services provided to users. The results of this research can guide libraries in developing policies and programs to improve librarian performance and the efficiency and overall quality of library services.